Continuous improvement in the footwear industry using the Six Sigma methodology. Case study: “Exclusivos Botero” (Ingeniería, Sostenibilidad y Sociedad, 2020)
This project focuses on the use of a qualitative review using the Six Sigma methodology for the footwear industry in the city of San José de Cúcuta. It analyzes the qualities and competitive advantage indices of an organization that implements these practices and the possible changes they experience in an increasingly dynamic market. At the same time, it focuses on a real case study of the planning of the methodology in production processes to achieve continuous improvement.
Keywords: Six sigma; Continuous improvement; PEPSU; SIPOC; DMAIC; Ishikawa